Real-world retrospective observational study exploring the effectiveness and safety of antifibrotics in idiopathic pulmonary fibrosis - Dhruv Parekh; David R Thickett; Peter Nightingale; Louise E Crowley; Anjali Crawshaw; William Alexander Wright (BMJ Open Respiratory Research)
Background Pirfenidone and nintedanib are the only disease-modifying treatments available for idiopathic pulmonary fibrosis (IPF). Our aim was to test their effectiveness and safety in clinical practice.Methods This is a single-centre retrospective observational study undertaken at a specialised interstitial lung disease centre in England. Data including progression-free survival (PFS), mortality and drug tolerability were compared between patients with IPF on antifibrotic therapies and an untreated control group who had a forced vital capacity percentage (FVC %) predicted within the licensed antifibrotic treatment range.Results 104 patients received antifibrotic therapies and 64 control patients were identified. PFS at 6 months was significantly greater in the antifibrotic group (75.0%) compared with the control group (56.3%) (p=0.012). PFS was not significant at 12 or 18 months when comparing the antifibrotic group with the control group. The 12-month post-treatment mean decline in FVC % predicted (−4.6±6.2%) was significantly less than the 12-month pretreatment decline (−10.4±11.8%) (p=0.039). The 12-month mortality rate was not significantly different between the antifibrotic group (25.3%) and the control group (35.5%) (p=0.132). Baseline Body Mass Index of≤25, baseline diffusion capacity for carbon monoxide percentage predicted of ≤35 and antifibrotic discontinuation within 3 months were independent predictors of 12-month mortality. Antifibrotic discontinuation was significantly higher by 3 and 6 months for patients on pirfenidone than those on nintedanib (p=0.006 and p=0.044, respectively). Discontinuation at 12 months was not significantly different (p=0.381).Conclusions This real-world study revealed that antifibrotics are having promising effects on PFS, lung function and mortality. These findings may favour commencement of nintedanib as first-line antifibrotic therapy, given the lower rates of early treatment discontinuation, although further studies are required to investigate this.